2013
DOI: 10.2341/12-521-l
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Enamel and Dentin Shear Bond Strengths of Current Dental Bonding Adhesives From Three Bond Generations

Abstract: As expected, fourth- and sixth-generation DBAs generally showed stronger SBS values than the seventh-generation all-in-one DBAs. The new sixth-generation DBA OptiBond XTR (Kerr) showed strong SBS values to both substrates and performed well in comparison to the other DBAs tested.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 12 publications
(13 reference statements)
3
20
0
Order By: Relevance
“…This is in agreement with previous studies that assessed the mechanical properties of adhesive-enamel interfaces (Beloica et al, 2010;Walter et al, 2011;Hanabusa et al, 2012;Goracci et al, 2013;Meharry et al, 2013;de Goes et al, 2014;McLean et al, 2015), although some conventional bond-strength studies reported similar values for 2-SEa and 1-SEa (Reis et al, 2013;de Goes et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This is in agreement with previous studies that assessed the mechanical properties of adhesive-enamel interfaces (Beloica et al, 2010;Walter et al, 2011;Hanabusa et al, 2012;Goracci et al, 2013;Meharry et al, 2013;de Goes et al, 2014;McLean et al, 2015), although some conventional bond-strength studies reported similar values for 2-SEa and 1-SEa (Reis et al, 2013;de Goes et al, 2014).…”
Section: Discussionsupporting
confidence: 92%
“…The finding that an E&R approach is more effective at enamel than a SE bonding protocol correlates well with previous enamel bondingeffectiveness studies (El Zohairy et al, 2010;Juloski et al, 2012;Schlueter et al, 2013;de Goes et al, 2014). Other studies that employed mSBS or mTBS test protocols were however not always able to distinguish between both approaches (El Zohairy et al, 2010;Walter et al, 2011;Meharry et al, 2013;Tedesco et al, 2014;Yaman et al, 2014). This study also demonstrated that multi-mode or universal adhesives, which up to the dentist's choice can be applied following either an E&R or SE mode, benefit most from phosphoric-acid etching of enamel; to effectively bond to enamel, universal adhesives are best applied following an E&R mode.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Such fractures are primarily within the restorative material, followed by fractures in the tooth [7,16,20,21]. In fact, adhesive cementation provides chemical and micro-mechanical attachment of the restoration to the tooth and re-establishes the integrity of the tooth and circumvents microleakage [2,24,25]. In that respect, sealing the dentin immediately after tooth preparation using a dentin bonding agent to the freshly cut dentin, the so called 'immediate dentin sealing (IDS)', was advocated in early 1990s [26].…”
Section: Introductionmentioning
confidence: 99%
“…Two-step self-etch adhesives have been further developed in recent years, and two two-step self-etch adhesives, OptiBond XTR (Kerr, Orange, CA, USA) and Clearfil SE Bond 2 (Kuraray Noritake Dental), have been introduced to the profession with the claim that they exhibit superior bonding performance to the previous generations of two-step self-etch adhesives, including Clearfil SE Bond. In the literature, Walter et al 17) and Meharry et al 18) reported that Optibond XTR showed superior enamel bond strength compared to Clearfil SE Bond. In addition, Sato et al 19) reported that the bond strength after 24 h and long-term (6 month and 1 year) water storage of Clearfil SE Bond 2, which is offered as an improved version of Clearfil SE Bond with a new photo-initiator, was higher than that of Clearfil SE, and that it showed a higher degree of conversion.…”
Section: Introductionmentioning
confidence: 99%